Methods applied by Russia to forecast the influence on other countries - Słowik, Jakub (Defence Science Review (Online), 2022)
Objectives The purpose of this article is to identify the quantitative and qualitative methods applied by Russia in planning exerting influence on other countries, including members of the Visegrád Group. Methods The research method used in this study consists in a systematic review of Russian and global political literature, as well as military literature, publications in the field of international relations, international politics, econometrics and forecasting, economy and management, in the aspect of the differences between the methods of forecasting the influence on other countries with respect to the methods described in international subject literature. Results The conducted analysis of documents enabled the identification and drawing the characteristics of the strategic forecasting methods that Russia may apply to influence other countries. The study also identifies the institutions as well as researchers who deal with the issues related to forecasting influence on specific countries in Russia. Conclusions Both the identified methods and the research centres focus on ensuring the effectiveness of Russian foreign policy that requires an accurate assessment of the current situation as well as detailed forecasts of potential events (scenarios) in the future. The method that deserves particular attention is the strategic matrix method, which has probably been modified, but its essential elements are still functioning.